Technology for creating a digital cartographic basis for information and assessment maps of the research area (Journal of Geography and Environmental Management, 2025)
The digital cartographic framework plays a key role in the creation of information and assessment maps that provide detailed and accurate geospatial data for the analysis, planning and management of territories. This article describes the technology of creating a digital cartographic framework, including the stages of data collection, processing, analysis and visualization. The methods of regular updating of thematic layers based on satellite images are considered, which ensures the relevance and reliability of cartographic information.Special attention is paid to the integration of various data sources, such as aerial photographs, satellite images and remote sensing data, which allows you to create a comprehensive and comprehensive picture of the studied area. The article emphasizes the importance of modern technologies and methods in creating informative and accurate cartographic products that contribute to sustainable development and effective management of natural and economic resources.The information and assessment maps created on the basis of the CCO play an important role in supporting decision-making related to the management of territories, ensuring environmental safety and sustainable development. Examples of successful application of the digital cartographic framework in various fields such as ecology, urbanism, agriculture and water resources management are also considered. Practical recommendations on the use of modern geoinformation systems (GIS) to improve the efficiency of management decision-making are given. The article focuses on the importance of an interdisciplinary approach and cooperation between various industry specialists, which allows to improve the quality and accuracy of the created cartographic products.
Keywords: digital cartographic basis; information and evaluation map; spectral indexes; geolocation; vectorization